O controle jurisdicional das omissões de prestações normativas do legislador em direitos fundamentais: aspectos teóricos - Gomes, Felipe Lima (2012)
The work analyses the most important theoretical aspects about judicial review of legislative omissions in the field of fundamental rights, specifically the normative commitments aiming at the consecution of these rights, and the results of this analysis in the interpretation of some mechanisms given by Brazilian Constitution to overcome these omissions. Two basic notions are studied in more detail, to clarify the discourse used throughout the study: legal competence and legal duty. The first is important because there is a legislative omissions when a legislator’s competence is not exercised (or it’s partially exercised); the second is important because legislative omissions are unconstitutional only if they disobey any duty to legislate imposed by constitutional norms (or, like some scholars prefer, if rests one legal situation contrary to constitutional norms). After this, it analyses the relation between fundamental rights and legislative discretion, in what matters to judicial control of legislative omissions. Robert Alexy’s theory of principles is adopted like the theoretical framework to represent the collisions between rights (material principles) and the (formal) principle of legislative discretion, with the purpose of clearing which (and how) is involved in the judicial review of legislative omissions. Thereafter, some solutions offered to the problem are exposed and confronted with the major argument against this control: the separation of powers. Finally, the results obtained along the study are applied to investigate the limits of Brazilian system of overcoming legislative omissions.